Sulfur disproportionation tendencies in a sulfur packed bed reactor for perchlorate bio-autotrophic reduction at different temperatures and spatial distribution of microbial communities. (January 2019) - Wan, Dongjin; Liu, Yongde; Wang, Yiyi; Li, Qi; Jin, Jingnan; Xiao, Shuhu
Abstract: This study investigates the sulfur (S) disproportionation tendencies in a sulfur packed bed reactor for perchlorate bio-autotrophic reduction at different temperatures. The reactor was operated with over 99% efficiency for 21.00 ± 1.40 mg L −1 perchlorate removal when the hydraulic retention time (HRT) ranged from 12.00 h to 0.75 h at 27 ± 2 °C. When HRT was controlled at 1.00 h, the perchlorate removal efficiency was only 8 ± 1% as the temperature dropped to 6 ± 1 °C. The half-order model fit both perchlorate removal and S disproportionation reaction well. Compared with S disproportionation, the decrease of temperature had a greater influence on perchlorate reduction. As the temperature dropped from 27 ± 2 °C to 6 ± 1 °C, the 1/2 K 1/2 v, R for perchlorate reduction decreased from 7.37 mg 1/2  L −1/2 h −1 to 0.19 mg 1/2  L −1/2 h −1 . Meanwhile, the 1/2 K 1/2 v, S for S disproportionation decreased from 3.04 mg 1/2  L −1/2 h −1 to 1.96 mg 1/2  L −1/2 h −1 . The reaction activation energy of perchlorate reduction and S disproportionation was 120.28 kJ mol −1 and 13.44 kJ mol −1, respectively. The S disproportionation reaction proceeded remarkably at the beginning of the reduction, a longer HRT and higher temperature promoted S disproportionation, resulting in excessive sulfate generation and alkalinity consumption. Besides, the spatial distribution of the microbial communities and the dominant bacteria function under different HRTs was analyzed using high-throughput sequencing. Graphical abstract: Highlights: The acceleration of S disproportionation was discovered. 21.00 mg/L ClO4 − was removed >99% at HRT 0.75 h (27 ± 2 °C). 1/2 kinetics model fit both perchlorate removal and S disproportionation well. Spatial distribution of the microbial communities was analyzed. Bacterial α and β diversity, and dominant genus was investigated.